A randomised crossover study comparing bimatoprost and latanoprost in subjects with primary angle closure glaucoma. Issue 6 (30th March 2009) - How, A C S; Kumar, R S; Chen, Y-M; Su, D H; Gao, H; Oen, F T; Ho, C-L; Seah, S K; Aung, T
Abstract : Background/aims: To compare the intraocular pressure (IOP) lowering efficacy and side effects of latanoprost 0.005% and bimatoprost 0.03% in subjects with chronic primary angle closure glaucoma (PACG). Methods: This was an observer-masked randomised crossover study of 60 PACG subjects who received either latanoprost or bimatoprost for 6 weeks, after which they were crossed over to the other medication for another 6 weeks. The IOP-reducing effect of the medications was assessed by the reduction in IOP after 6 weeks of treatment compared with baseline. Results: Fifty-four subjects (80 eyes) completed the study. Latanoprost reduced IOP (mean (SD)) by 8.4 (3.8) mm Hg and bimatoprost by 8.9 (3.9) mm Hg from a baseline of 25.2 (3.6) mm Hg and 25.2 (3.6) mm Hg respectively (p = 0.23). Adverse events were mild in both groups; however there were twice as many reports of an adverse event in the bimatoprost group (81%) compared with the latanoprost group (40%, p<0.01). Ocular irritation was the most frequently reported adverse event in both groups; 22 subjects (37.9%) treated with bimatoprost experienced ocular hyperaemia as compared with 13 subjects (22.4%) treated with latanoprost (p = 0.11). Conclusions: Bimatoprost once daily was similarly effective in reducing IOP compared with latanoprost once daily in subjects with chronic PACG. Both drugs were well tolerated with mild ocular adverse events.